2020
DOI: 10.1161/jaha.120.016122
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures and Cardiac Structure and Function: ECHO‐SOL (Echocardiographic Study of Latinos)

Abstract: Background Our objective was to determine associations of occupational exposures with cardiac structure and function in Hispanic/Latino adults. Methods and Results Employed participants were included (n=782; 52% women, mean age 52.9 years). Occupational exposures to burning wood, vehicle exhaust, solvents, pesticides, and metals at the current and longest‐held job were assessed by questionnaire. Survey multivariable linear regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…According to the report of the World Health Organization, almost 7 million people die due to air pollution every year, indicating air pollution to be the world's largest environmental health risk ( 7 ). Particulate matters (PM) and gases are the main components of air pollution that have been reported to induce stroke ( 8 ), myocardial infarction ( 9 ), HF, atrial fibrillation, and sudden cardiac death ( 10 ) in multiple populations. Air pollution-induced cardiovascular events have received more attention than other related toxicity, such as pulmonary diseases ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of the World Health Organization, almost 7 million people die due to air pollution every year, indicating air pollution to be the world's largest environmental health risk ( 7 ). Particulate matters (PM) and gases are the main components of air pollution that have been reported to induce stroke ( 8 ), myocardial infarction ( 9 ), HF, atrial fibrillation, and sudden cardiac death ( 10 ) in multiple populations. Air pollution-induced cardiovascular events have received more attention than other related toxicity, such as pulmonary diseases ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 In recent years, substantial evidence has pointed to the link between exposure to Ni compounds and vascular endothelial dysfunction. [18][19][20][21] Endothelial dysfunction is believed to contribute to the pathogenesis of the cardiovascular disease (CVD) and act as both the trigger and consequence of oxidative stress and inflammation. 22,23 24 Moreover, studies conducted by Vale and Scioli have shown that oxidative stress-induced inflammation is involved in endothelial dysfunction and increases the atherosclerosis burden.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, substantial evidence has pointed to the link between exposure to Ni compounds and vascular endothelial dysfunction 18–21 . Endothelial dysfunction is believed to contribute to the pathogenesis of the cardiovascular disease (CVD) and act as both the trigger and consequence of oxidative stress and inflammation 22,23 .…”
Section: Introductionmentioning
confidence: 99%